Altered relaxation times in MRI indicate bronchopulmonary dysplasia. Issue 2 (2nd May 2019) - Förster, Kai; Ertl-Wagner, Birgit; Ehrhardt, Harald; Busen, Hannah; Sass, Steffen; Pomschar, Andreas; Naehrlich, Lutz; Schulze, Andreas; Flemmer, Andreas W; Hübener, Christoph; Eickelberg, Oliver; Theis, Fabian; et al.
Abstract : We developed a MRI protocol using transverse (T2) and longitudinal (T1) mapping sequences to characterise lung structural changes in preterm infants with bronchopulmonary dysplasia (BPD). We prospectively enrolled 61 infants to perform 3-Tesla MRI of the lung in quiet sleep. Statistical analysis was performed using logistic Group Lasso regression and logistic regression. Increased lung T2 relaxation time and decreased lung T1 relaxation time indicated BPD yielding an area under the curve (AUC) of 0.80. Results were confirmed in an independent study cohort (AUC 0.75) and mirrored by lung function testing, indicating the high potential for MRI in future BPD diagnostics. Trial registration: DRKS00004600.